Gamma-ray character and correlation of the Lower Lias, SW Britain - Bessa, J; Hesselbo, S (1997)
A high-resolution outcrop to subsurface gamma-ray correlation of the Lower Lias across S\V Britain is presented. The study focuses upon the mud-dominated, fully marine Rhaetian to Pliensbachian succession that outcrops in the Bristol Channel and Wessex Basins. The succession has been divided into eighteen correlatable spectral gammaray units. Boundaries of the gamma-ray units do not cross time-lines inferred from the biostratigraphy. Correlation of the spectral gamma-ray units N-S across the Bristol Channel suggests a hiatus at the boundary of the planorbis and liasicus ammonite zones in Somerset relative to the coeval section in Glamorgan. The outcrop-based gamma-ray units have also been identified in the subsurface from total gamma-ray logs in both the Burton Row borehole, Somerset, and in the Winterborne Kingston borehole, Dorset. Correlation is therefore possible across numerous fault blocks and between different basins. © 1997 Geologists' Association.